Non-syndromic craniosynostosis: a retrospective analysis - Costa, Paulo Víctor Cunha [UNESP]; Secanho, Murilo Sgarbi [UNESP]; Pinheiro, Leon Cleres Penido [UNESP]; Santos, Marcelo Hanato [UNESP]; Palhares, Aristides Augusto [UNESP]; Hamamoto-Filho, Pedro Tadao [UNESP] (Thieme, 2020)
Introduction: Craniosynostoses are defined as premature fusions of one or more cranial sutures. They can be classified according to the sutures involved, correlated malformations and genetic alterations, and maybe syndromic or not. Its incidence is estimated at 1: 2,000-2,500 live births, with only 8% being syndromic. There are multiple surgical options for the correction of these malformations, and early referral to specialized centers for the treatment of these patients is necessary for a better therapeutic indication. The diagnosis is based on physical examination and computed tomography. The surgical treatment brings significant aesthetic and social improvements to patients. The objective is to analyze retrospectively patient data who underwent surgery to correct craniosynostosis at HC of UNESP-Botucatu. Methods: Retrospective analysis of the medical records of patients who underwent surgical correction of craniosynostosis between 2012 and 2017. Results: The prevalence of scaphocephaly and trigonocephaly was the same (38.5%). The mean age of the approach was 24 months; the mean surgical time was 3h48min, lower in scaphocephaly, 2h50min. All patients received blood transfusions in the perioperative period, with a mean percentage of 24.9% in relation to the preoperative blood volume. They underwent postoperative in a pediatric ICU. There were no deaths or complications, and the results were considered good by the team and family. Conclusion: Open surgical treatment of non-syndromic craniosynostosis is a safe procedure. Plastic surgery teams can achieve results comparable to those described in the literature, with low complication rates, good aesthetic results when performed correctly and with a multidisciplinary approach.
Craniossinostoses não sindrômicas: uma análise retrospectiva
Keywords: Blood transfusion; Craniofacial abnormalities; Craniosynostoses; Skull; Surgery, Plastic